Wholegrain Durum Wheat Bread Fortified With Citrus Fibers: Evaluation of Quality Parameters During Long Storage - Spina, Alfio; Brighina, Selina; Muccilli, Serena; Mazzaglia, Agata; Fabroni, Simona; Fallico, Biagio; Rapisarda, Paolo; Arena, Elena (Frontiers in Nutrition, 2019)
The aim of this work was to evaluate the effect of the addition of citrus fibers, from blood orange and lemon peels to produce a functional durum wheat bread. Breads fortified in fiber were packaged under a modified atmosphere (MAP) and stored at 25°C up to 120 days. No significant differences were observed with respect to the specific volume and weight, internal structure, pH and titratable acidity among the bread samples obtained using different types and percentages of fibers. Storage time, at 30 up to 90 days, affected significantly the bread firmness and caused significant differences in 5-hydroxymethylfurfural (HMF) levels in all bread samples. In fortified breads with citrus fibers the yeast and mold counts showed values of approximately 1 log10 cfu/g for the first 30 days and 3.5 log10 cfu/g at the end of storage. The results of the sensory evaluation highlight that loaves enriched with blood orange and lemon fibers showed a citrus flavor but had a similar overall evaluation respect to control bread produced without addition of citrus fiber. The results of this study showed that the addition up to 2% of blood orange and lemon fibers in wheat whole durum flour is a possible strategy to produce “high fibre” bread.